PENERAPAN STRATEGI KWHLAQ (KNOW-WHAT-HOW-LEARN-ACTIONS-QUESTIONS) UNTUK MENINGKATKAN RASA INGIN TAHU, PEMAHAMAN MEMBACA CERITA ALKITAB, DAN KEMAMPUAN BERPIKIR REFLEKTIF PADA PELAJARAN PENDIDIKAN AGAMA KRISTEN [THE IMPLEMENTATION OF THE KWHLAQ (KNOW-WHAT-HOW-LEARN-ACTIONS-QUESTIONS) STRATEGY TO IMPROVE STUDENTS’ CURIOSITY, READING COMPREHENSION, AND REFLECTIVE THINKING SKILLS IN BIBLICAL STUDIES EDUCATION] - Lina Tejo Sugiarto (Jurnal Teropong Pendidikan, 2021)
In XYZ elementary school, most grade 2 students show a lack of curiosity when learning Bible as a study subject, which cause the low participation score in learning that subject. Those students also show difficulties when doing the summative test which is caused by their deficiency in comprehending the written Bible story. Moreover, the students show minimum reflective thinking skill which needs to be noticed because the skill is important for learning process in the class. Those reasons show that grade 2 students’ curiosity, reading comprehension and reflective thinking skill when learning Biblical Studies need to be improved. KWHLAQ is a well-known strategy which is suitable to be used in improving the students’ curiosity, reading comprehension and reflective thinking skill. Therefore, this research was conducted to know the difference of students’ curiosity, reading comprehension and reflective thinking skill before and after using the KWHLAQ strategy. The research design used a quantitative, experimental one group pretest and posttest method. The subject of this research were 25 students of XYZ Elementary School – grade 2A which consist of 13 boys and 12 girls. The sample were chosen using purposive sampling technique. The data were analyzed with descriptive and inferential statistics (Paired Sample T-test and Wilcoxon Signed Ranks). The results showed that there were differences in grade 2A students’ curiosity, reading comprehension, and reflective thinking skill in learning Biblical studies after applying the KWHLAQ strategy.BAHASA INDONESIA ABSTRACT: Kurangnya rasa ingin tahu siswa pada pelajaran Pendidikan Agama Kristen (PAK) di SD XYZ menyebabkan rendahnya nilai partisipasi siswa dalam pelajaran PAK. Pemahaman membaca Alkitab juga kurang ditumbuhkan dalam diri siswa terlihat dari kesulitan siswa mengerjakan tes sumatif. Kurangnya kemampuan berpikir reflektif siswa perlu mendapat perhatian dalam pembelajaran di kelas. Hal ini menunjukkan bahwa rasa ingin tahu, pemahaman membaca, dan kemampuan berpikir reflektif siswa dalam pelajaran PAK di SD XYZ perlu ditingkatkan. Strategi KWHLAQ adalah strategi yang sangat baik diterapkan dalam pembelajaran PAK untuk meningkatkan rasa ingin tahu, pemahaman siswa, dan kemampuan berpikir reflektif siswa. Penelitian ini bertujuan untuk mengetahui perbedaan rasa ingin tahu, pemahaman membaca, dan kemampuan berpikir reflektif siswa dengan menggunakan strategi KWHLAQ. Penelitian ini merupakan penelitian kuantitatif dengan menggunakan metode eksperimental. Desain penelitian yang digunakan adalah one-group pretest-posttest. Subyek penelitian terdiri dari 25 siswa terdiri dari 13 laki-laki dan 12 perempuan yang seluruhnya berasal dari siswa kelas 2A SD XYZ Jakarta Barat. Teknik pengambilan sampel menggunakan purposive sampling. Data dianalisis dengan menggunakan statistik deskriptif dan inferensial (Uji Paired Sample T-test dan Uji Wilcoxon). Temuan penelitian mengungkapkan adanya perbedaan rasa ingin tahu, pemahaman membaca, dan kemampuan berpikir reflektif siswa kelas 2A SD XYZ dalam pelajaran PAK sesudah penerapan strategi KWHLAQ.